Исторические аспекты возникновения магнитно-импульсного притяжения тонкостенных листовых металлов - Батыгин, Ю.В.; Гнатов, А.В. (Електротехніка і електромеханіка, 2011)
In the article, origination of a new direction in Electrical Magnetic Metal Forming such as magnetic pulse attraction of thinwall sheet metals is analyzed. Patent No. 3,196,649 (H.Furth, 1965) claim is commented. Practical realization of the suggestion is shown impossible. The idea of utilization of two sources of (high-frequency and low-frequency) electromagnetic field for sheet metals magnetic pulse attraction is analyzed.